Transcriptional and epigenetic regulation of microglia in maintenance of brain homeostasis and neurodegeneration - Maurya, Shashank Kumar; Gupta, Suchi; Mishra, Rajnikant (Frontiers in Molecular Neuroscience, 2023)
The emerging role of microglia in brain homeostasis, neurodegeneration, and neurodevelopmental disorders has attracted considerable interest. In addition, recent developments in microglial functions and associated pathways have shed new light on their fundamental role in the immunological surveillance of the brain. Understanding the interconnections between microglia, neurons, and non-neuronal cells have opened up additional avenues for research in this evolving field. Furthermore, the study of microglia at the transcriptional and epigenetic levels has enhanced our knowledge of these native brain immune cells. Moreover, exploring various facets of microglia biology will facilitate the early detection, treatment, and management of neurological disorders. Consequently, the present review aimed to provide comprehensive insight on microglia biology and its influence on brain development, homeostasis, management of disease, and highlights microglia as potential therapeutic targets in neurodegenerative and neurodevelopmental diseases.